Effects of aerobic training with and without weight loss on insulin sensitivity and lipids - Damon L. Swift; Joseph A. Houmard; Cris A. Slentz; William E. Kraus (2018)
Purpose The purpose of this study is to evaluate the effect of exercise training with modest or greater weight loss (≥3%) or not (<3%) on insulin sensitivity, lipoprotein concentrations, and lipoprotein particle size in overweight and obese participants. Methods Adults (N = 163, body mass index: 25–37 [kg/m2]) participated in 8 months of exercise training. Insulin sensitivity, lipid concentrations, lipid particle size and other cardiometabolic variables were measured at baseline and follow-up. Participants were categorized by whether they achieved at least modest weight loss (≥ 3%) or not (<3%) following the intervention. Results A greater improvement in insulin sensitivity was observed in adults performing exercise training with at least modest weight loss (2.2 mU·l-1 ·min -1, CI: 1.5 to 2.8) compared to those who did not (0.8 mU·l-1 ·min -1, CI: 0.5 to 1.2). Similar results were observed for acute insulin response, triglycerides, non-HDL cholesterol concentration, low density lipoprotein (LDL) particle size and high density lipoprotein (HDL) particle size (p<0.05), when all exercise groups were combined. No significant results across weight loss categories were observed for LDL, HDL, glucose, or insulin levels. Conclusion The present study suggests that aerobic exercise combined with at least modest weight loss leads to greater improvements in insulin sensitivity, triglycerides as well as other non-traditional lipid risk factors (non-HDL cholesterol, HDL/LDL particle size). Clinicians should advocate patients who are overweight/obese to exercise and obtain modest weight loss for improved cardiovascular benefits.